“Neo-Kkn” Dan Tantangan Demokratisasi Indonesia - Irham, Muhammad Aqil (Analisis: Jurnal Studi Keislaman, 2016)
This article outlines the still-scattered problems related to the phenomenon of democracy in Indonesia. Entering the New Order era, democracy found its momentum. The revolt of political ideology happens from authoritarianism to democracy. However, some diseases of earlier times seem to appears in such a new form in the present. The disease is still terait KKN (Korpusi, Collusion and Nepotism) clad in various issues like ecentralization and democratization. This article aims to unravel the the linkage between the phenomenon of neo-corruption  and  democratization  in  Indonesia.  Using the perspective of Mark Warren, generic relation between corruption and democracy will be described, including several strategic steps in tackling these problems